Systematic review of archivists’ evolving ethics in the age of artificial intelligence - Sanbein, Primus (Jurnal Kajian Informasi dan Perpustakaan, 2025)
The development of artificial intelligence (AI) in the field of archiving raises new ethical challenges, such as algorithmic bias, loss of human context, and unclear accountability. Therefore, a systematic literature review is needed to understand how the ethics and professional values of archivists evolve in the face of AI-based digital transformation. This study aimed to determine how the ethics and professional values of archivists evolved in the era of artificial intelligence through an analysis of thematic patterns, ethical issues, and strategic responses that arose from human and AI interactions in archival practice. This study used the systematic literature review (SLR) method with reference to the PRISMA protocol. A total of 50 indexed and peer-reviewed journal articles published between 2018 and 2025 were analyzed, obtained from academic databases such as Scopus, SpringerLink, and Taylor & Francis. The analysis revealed five key domains: shifting roles and identities of archivists, reconfiguration of ethical principles in digital practice, dynamics of human–AI collaboration, reconstruction of professional values in an AI-based ecosystem, and strategic implications for strengthening the profession. The study concludes that archivists not only need to adapt to AI but also play an active role in guiding its implementation through ethical design, enhancing digital and ethical literacy, and updating professional codes of conduct. These efforts are essential to maintaining public trust, ensuring professional accountability, and ensuring the sustainability of the archivist’s role in an increasingly automated digital society.